Sub‐Toxic Nicotine Concentrations Affect Extracellular Matrix and Growth Factor Signaling Gene Expressions in Human Osteoblasts. Issue 12 (December 2014) - Marinucci, Lorella; Bodo, Maria; Balloni, Stefania; Locci, Paola; Baroni, Tiziano
<x xml:space="preserve">Abstract</x> Exposure to nicotine and other compounds contained in cigarette smoking affects human health. This study examined the effects of exposure to a single or multiple sub‐toxic nicotine concentrations on human osteoblasts. Cell growth and expression of genes involved in bone differentiation, extracellular matrix (ECM) metabolism, and growth factor signaling pathways were investigated in nicotine‐treated cells compared to untreated cells. Depending on osteoblast concentration and maturation stages, nicotine differently regulated cell growth. Real‐time PCR showed regulated expressions of genes expressed by nicotine‐treated osteoblasts compared to untreated cells. Among ECM genes, type I collagen was down‐regulated and osteonectin was up‐regulated in nicotine‐treated osteoblasts; similarly, fibroblast growth factor‐1 (FGF1) and fibroblast growth factor‐2 (FGF2), two members of FGF signaling system, were discordantly modulated; genes involved in osteoblast maturation and differentiation such as alkaline phosphatase (ALP), runt‐related transcription factor‐2 (RUNX2), and bone sialoprotein (BSP) were over‐expressed after drug treatment. Our results show a positive association between nicotine exposure and osteoblast phenotype and illustrate for the first time a mechanism whereby acute or chronic exposure to sub‐toxic nicotine concentrations may affect bone formation through the impairment of growth factor signaling system and ECM metabolism. J. Cell. Physiol. 229: 2038–2048, 2014. © 2014 Wiley Periodicals, Inc.